This land is our land? This land is your land : exploring the decolonizing journeys of White outdoor environmental educators - Root, Emily (My University, 2009)
My own decolonizing journey has fostered a curiosity about the experiences of other White outdoor environmental educators who are engaged in the process of decolonizing their own practices and worldview. This qualitative study explored the nature of "decolonizing moments" in the lives of four White outdoor environmental educators. It addresses the overarching questions: What is the nature of the decolonizing journeys of White outdoor environmental educators? And what life experiences facilitate this process? The research process itself also served as a decolonizing experience as the study engaged both the researcher and the participants in a reflexive experience that was intended to refine our decolonizing lenses and help us to further decolonize our teaching praxis.
Keywords: Outdoor Education; Canada; Environmental education; Research; Native Peoples; Indigenous peoples; Indians of North America; Eurocentricism; Decolonization